Model Kolaboratif Penanggulangan Kemiskinan Ekstrem melalui Konsep Hexahelix di Provinsi Papua Barat Daya - La Ibal; Rahful A. Madaul; Nabila Nur Rifqah (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2023)
Southwest Papua Province, part of Indonesia, faces significant developmentalchallenges, especially extreme poverty influenced by its adherence tocustomary law. With a poverty rate of 14.2 percent, this research employsproblem-solving methods like qualitative and descriptive approaches. Thestudy reveals a collaborative approach to combat extreme poverty in the region,involving various stakeholders and supported by additional contributors. Thiscoalition includes regional authorities, academics, businesses, privateindividuals, media, communities, and traditional institutions. Further supportcomes from banks, NGOs, markets, local industries, and small-scaleentrepreneurs. Each party has a distinct role: the government oversees,academics provide frameworks, businesses support, communities driveprogress, media spreads information, and traditional institutions planinterventions. This multi-stakeholder strategy is crucial in addressing extremepoverty in Southwest Papua Province, harnessing diverse roles for sustainablechange.